I was also a founder of UNA - Quesada Monge, Rodrigo (2025)
This text is a reflection on the author’s experience at the National University (UNA) of Costa Rica, an institution that provided him with professional orientation, ideological and human formation. He mentions how the world context provoked several ideological crises, which overthrew his convictions on political and military issues and, of course, his own vision of the world. He highlights his participation in different activities related to communism, as well as the new perspectives that political conditions forced him to seek: conservatism and liberalism. His trajectory in the UNA took it as a fundamental step for his development, observing it as a space for intellectual reflection in the midst of the political and social chaos that the country went through during the decades that marked the twentieth century.